Rieszov funkcijski račun - Gladek, Žiga (Matrika, 2023)
In this work the construction of the Riesz functional calculus is examined, which is a generalization of the calculus that evaluates holomorphic functions in matrices. In order to achieve this, the notions of spectrum and holomorphic function are generalized to the setting of Banach algebras. Most of the ordinary results from complex analysis transfer to this setting which allows us to define a functional calculus using the line integral.
Keywords: holomorfne funkcije; holomorphic functions; Riesz functional calculus; Rieszov funkcijski račun